Bank capital requirements and collateralised lending markets - Rubio, Margarita; Carrasco-Gallego, José A. (Wiley, 2017)
In this paper, we take as a baseline a dynamic stochastic general equilibrium (DSGE) model, which features a housing market, borrowers, savers and banks, in order to evaluate the welfare and macroeconomic effects of the new fixed capital requirements in the Basel accords. Our results show that the higher capital requirements imposed by Basel I, II and III decrease both the quantity of borrowing and its variability, producing distributional welfare effects among agents: savers are better o¤, but borrowers and banks are worse o¤. Then, we propose a macroprudential rule for the counter- cyclical capital buffer of Basel III in which capital requirements respond to credit growth, output and housing prices. We find that the optimal implementation of Basel III is countercyclical for borrowers and banks, the agents directly affected by capital requirements, while procyclical for savers. From a normative perspective, we see that this macroprudential rule for Basel III delivers higher welfare for the society than a situation with no regulation.